Effects of maturation and scarification on seed germination of Syagrus schizophylla (Mart.) glass. (Arecaceae) - Pivetta, KFL; de Paula, R. C.; Cintra, G. S.; Pedrinho, D. R.; Casali, L. P.; Pizetta, PUC; Sarzi, I; Pimenta, R. S. (International Society Horticultural Science, 2005)
Syagrus schizophylla (Mart.) Glass. belongs to the Arecaccae family. This palm is native of Brazil and presents great potential for use in gardens and cultivation in pot. Palms species, with relatively few exceptions, can only be propagated from seeds; even so, there are no reports in the literature about the germination of this palm seeds. The seed maturity is a factor that interferes in the success of the germination process. For some species, studies showed that palm seeds germinated better when the fruits were completely ripe (showing full color) and for other, when they were with green coloration. Several species of the Arecaccae family presents physical dormancy of seeds in varied degrees, demanding treatments for improve germination. The objective of this work was to study the effects of maturation and of the scarification on seed germination of S. schizophylla. The experimental design used was a factorial 3 x 2 (3 maturation stadiums: green, half-ripe - yellow and completely ripe - red; and mechanical scarification: with and without), entirely casualized, with four replications of 15 seeds per plot. The seeds (with 32,43% of humidity) were placed in plastic boxes with sand (60% of humidity, placing water according to weight in each three days), under controlled conditions of alternated temperature of 25-35 degrees C, photoperiod of 12 hours. The percentage of germination and the speed germination index (SGI) were evaluated until 79 days. It was observed that, so much for germination percentage as for SGI, there was not significant difference for the interaction among the two factors, maturation stadium and scarification, however, there were significant differences among the maturation stadiums and between seeds scarified or not. The seeds from green fruits presented lower germination percentage and slower germination when compared with seeds from yellow or red fruits; the seeds from yellow or red fruits didn't differ statistically to each other. To seeds scarificated, independently of the maturation stadium, presented germination percentage significantly larger and the germination was significantly faster when compared with the seeds without scarification.
Keywords: propagation; ornamental palm